Meningkatkan Literasi dan Pentingnya Pendidikan terhadap Anak Didik (Lembaga Pengembangan Kinerja Dosen, 2025)
The independent real college work (KKN) of Muhammadiyah Sumatra Utara was carried out at MTS Al-Washliyah, Hamparan Perak sub-district, Deli Serdang district. This KKN program aimed to improve literacy and highlight the importance of education for children’s abilities in both character development and student intelligence. The goal of education is to advance intellectual development while instilling moral values, ethics, integrity, and tolerance in students. The results of this study indicate that the role of parents is crucial in developing literacy in students. Parents are encouraged to help children develop a habit of reading books, thus providing a positive influence on their children's educational progress. Additionally, parents' active involvement allows children to have better opportunities to develop their literacy skills. By creating a supportive home environment and fostering positive reading habits, parents play a vital role in improving the overall literacy of students. This KKN program has shown that collaboration between parents and educational institutions can significantly enhance the literacy development of students.